Clinical significance of early echocardiography after out-of-hospital cardiac arrest on arrival to a heart attack centre. (14th October 2021) - Kanyal, R; Sarma, D; Pareek, N; Dworakowski, R; Melikian, N; Webb, I; Shah, A; MacCarthy, P; Byrne, J
Abstract: Background: Left ventricular systolic dysfunction (LVSD) is common after out of hospital cardiac arrest (OOHCA) and can manifest as global or regional change. Purpose: We evaluated the extent of global and regional LVSD and its association with coronary artery disease (CAD) and outcome in those undergoing coronary angiography after OOHCA. Methods: 619 patients with OOHCA were admitted at our centre between 1st May 2012 and 31st December 2017. 398 patients were included. Rates of cardiogenic shock and extent of CAD, as classified by the SYNTAX score were measured. The primary endpoint was 12-month mortality. Patients with incomplete data were excluded from the analysis. Results: Two hundred and sixty-six patients (median age 62 [53–71] 76.3% male) underwent both trans-thoracic echocardiography andcoronary angiography on arrival and were included in the final analysis. 81.6% had ventricular fibrillation, 83.5% were witnessed and 51.9% occurred at residence. Ninety-six patients (36%) had significant LVSD (Left Ventricular Ejection Fraction [LVEF] <40%) and 139 (52.2%) patients had regional wall motion abnormalities (RWMAs) on arrival. Patients were classified into 4 groups (Group A: LVEF <40%/Global, Group B: LVEF <40%/RWMA, Group C: LVEF ≥40%/Global and Group D: LVEF ≥40%/RWMA) with frequencies of 10.9%, 25.2%, 41.4% and 22.6%). Patients in Group D had the shortest low-flow times and lowest rates of epinephrine administration, with most favourable metabolic status on arrival, based on lactate and creatinine values. In Groups B and D (RWMAs), patients were significantly more likely to have a post-ROSC ECG demonstrating ST elevation/LBBB and absence of epinephrine administration during resuscitation with shorter low flow times. Extent of CAD was similar between the four groups. From patients with LVEF ≥40%, patients in Group C had substantially lower SYNTAX scores than compared with Group D (0.5 vs 13.5, p<0.001). However, both Group B and C (RWMA) groups had highest rates of culprit lesions compared with matched global groups which was reflected in higher PCI rates (Figure 1). The primary endpoint of 12-month mortality was lowest in Group D and highest in the Group A group. A similar effect was observed for poor neurological outcome and 30-day mortality. Patients with regional LVSD had significantly improved survival at 12 months compared with those with global LVSD (70.5% vs 48.3%, p<0.001) vs 51). Those in Group D had highest survival at 12 months, while this was similar for Groups B and C and lowest in Group A (Figure 2). Cardiac aetiology death was significantly higher in those with LVEF <40% compared to those with LVEF ≥40% (70.5% vs 48.3%, p<0.001). Conclusions: Patients with significant LVEF <40% have higher rates of cardiogenic shock and mortality which was driven by cardiac aetiology death, while presence of RWMAs are associated with a higher rate of culprit coronary lesions and improved outcome FUNDunding Acknowledgement: Type of funding sources: None.